Rhodes - Huston, Walter 1884-1950; Homolka, Oscar 1898-1978; Sydney, Basil 1894-1968 (Rhodesian Broadcasting Corporation, 2015)
Portrays the life of British imperialist and business magnate, Cecil Rhodes
Originally produced as a motion picture in 1936
Keywords: Rhodes, Cecil / 1853-1902; Africa, Southern / History / 19th century; Feature films; Biographical films; Southern Africa; 1800-1899; History